Does bank competition influence the lending channel in the euro area - Zuzana Fungáčová; Laura Solanko; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper examines how bank competition influences the bank lending channel in the Euro area countries. Using a large panel of banks from 12 euro area countries over the period 2002?2010 we analyze the reaction of loan supply to monetary policy actions depending on the degree of bank competition. We find that the effect of monetary policy on bank lending is dependent on bank competition: the transmission of monetary policy through the bank lending channel is less pronounced for banks with extensive market power. Further investigation shows that banks with less market power were more sensitive to monetary policy only before the financial crisis. These results suggest that the bank market power has a significant impact on monetary policy effectiveness. Therefore, wide variations in the level of bank market power may lead to asymmetric effects of a single monetary policy.
URN:NBN:fi:bof-201408071983
Keywords: E52; G21; 330; bank competition; bank lending channel; monetary policy; euro area